Use of a digital rescue inhaler and at-home spirometer among inner-city children with asthma: a real-world experience - Izadi, Neema; Hill, Tanisha D.; Boe, Amanda; Yu, Daisy; Tam, Jonathan S. (Frontiers in Allergy, 2025)
BackgroundAcross all age groups, asthma disproportionally affects inner-city underserved populations. Studies on the use of at-home spirometry and digital inhalers have limited real-world evaluation in pediatric asthma.ObjectivesIn this prospective exploratory study, we assessed how an integrated digital rescue inhaler and at-home spirometer would affect proper inhaler use, medication adherence, and asthma outcomes using a minimalistic real-world approach.MethodsIn total, 21 pediatric patients with asthma (8–17 years of age) were asked to replace rescue medications with the ProAir Digihaler and perform at-home gamified spirometry daily. Lung function and questionnaires were obtained at baseline and at 3–4 months.ResultsThe participants were mostly male (81%), Latino/Hispanic (71%), and obese (88th ±16 percentile). Proper rescue inhaler step identification by survey did not change, but inhalation technique based on digital inhaler flow measurements improved for all participants. At-home spirometry was sporadic and reported controller adherence did not change. Younger children (age 8–11) were more severe at baseline [Composite Asthma Severity Index (CASI) of 4.8] compared to older children (CASI of 2.9). For younger children, overall asthma control test scores increased by 3.1, CASI decreased by 0.70, and the Pediatric Quality of Life Inventory scores increased by 14 and 11 for participants and parents, respectively.ConclusionsProper rescue inhaler step identification by survey did not change, but actual inhalation technique based on digital inhaler flow measurements improved. At-home spirometry was sporadic and reported medication adherence did not change. Younger children used the spirometer more frequently and demonstrated improvements in asthma control, severity, and quality of life. These improvements were not observed in older children.